Effects of an Eight-Week Superimposed Submaximal Dynamic Whole-Body Electromyostimulation Training on Strength and Power Parameters of the Leg Muscles: A Randomized Controlled Intervention Study - Micke, Florian; Kleinöder, Heinz; Dörmann, Ulrike; Wirtz, Nicolas; Donath, Lars (Frontiers in Physiology, 2018)
The purpose of this study was to assess the effects of dynamic superimposed submaximal whole-body electromyostimulation (WB-EMS) training on maximal strength and power parameters of the leg muscles compared with a similar dynamic training without WB-EMS. Eighteen male sport students were either randomly assigned to a WB-EMS intervention (INT; n=9; age: 22.8 ± 3.0 years; body mass: 80.2 ± 6.6 kg; strength training experience: 4.6 ± 2.8 years) or a traditional strength training group (CON; n=9; age: 22.8 ± 2.5 years; body mass: 77.6 ± 9.0 kg; strength training experience: 4.5 ± 2.9 years). Both training intervention programs were performed 2 times a week over a period of 8 weeks with the only difference that the INT group performed all dynamic exercises (e.g., split squats, glute-ham raises, jumps, tappings) with superimposed WB-EMS. WB-EMS intensity was adjusted to 70% of the individual maximal pain threshold to ensure dynamic movement. Before (PRE), after (POST) and 2 weeks after the intervention (FU), performance indices were assessed by maximal strength (Fmax) and maximal power (Pmax) testing on the leg extension (LE), leg curl (LC) and leg press (LP) machine as primary endpoints. Additionally, vertical and horizontal jumps and 30m sprint tests were conducted as secondary endpoints at PRE, POST and FU testing. Significant time effects were observed for strength and power parameters on LE and LC (LE Fmax +5.0%; LC Pmax +13.5%). A significant time x group interaction effect was merely observed for Fmax on the LE (p=0.029; ηp²=0.211) where follow-up post-hoc testing showed significantly higher improvements in the INT group from PRE to POST and PRE to FU (INT: +7.7%, p<0.01; CON: +2.1%). The findings of this study indicate that the combination of dynamic exercises and superimposed submaximal WB-EMS seems to be effective in order to improve leg strength and power. However, in young healthy adults the effects of superimposed WB-EMS were similar to the effects of dynamic resistance training without EMS, with the exception of a significantly greater increase in leg extension Fmax in the WB-EMS group.